1996
DOI: 10.1111/j.1432-1033.1996.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Enzymes Involved in Chlorophyll Biosynthesis

Abstract: All living organisms contain tetrapyrroles. In plants, chlorophyll (chlorophyll a plus chlorophyll b) is the most abundant and probably most important tetrapyrrole. It is involved in light absorption and energy transduction during photosynthesis. Chlorophyll is synthesized from the intact carbon skeleton of glutamate via the C, pathway. This pathway takes place in the chloroplast. It is the aim of this review to summarize the current knowledge on the biochemistry and molecular biology of the C,-pathway enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(56 citation statements)
references
References 329 publications
(291 reference statements)
3
50
0
3
Order By: Relevance
“…The biosynthesis of tetrapyrrole (porphyrins and chlorins) via the C5-pathway, a process taking place entirely in chloroplasts, was found to have three potential thioredoxin-linked members: glutamate-1-semialdehyde 2,1-(GSA)-aminomutase, uroporphyrinogen decarboxylase, and magnesium chelatase. The first of these, glutamate-1-semialdehyde 2,1 aminomutase, catalyzes the formation of ␦-aminolevulinic acid, the first committed precursor of the C5-pathway (21). Other evidence supports such a role for thioredoxin in this series of reactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The biosynthesis of tetrapyrrole (porphyrins and chlorins) via the C5-pathway, a process taking place entirely in chloroplasts, was found to have three potential thioredoxin-linked members: glutamate-1-semialdehyde 2,1-(GSA)-aminomutase, uroporphyrinogen decarboxylase, and magnesium chelatase. The first of these, glutamate-1-semialdehyde 2,1 aminomutase, catalyzes the formation of ␦-aminolevulinic acid, the first committed precursor of the C5-pathway (21). Other evidence supports such a role for thioredoxin in this series of reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Other evidence supports such a role for thioredoxin in this series of reactions. For example, the activity of glutamate-1-semialdehyde aminomutase in etiolated barley seedlings increases dramatically in the light whereas the level of the corresponding mRNA remains constant (21). Further, it has been observed that DTT alleviates the inhibition of the synthesis of an intermediate of the pathway, protoporphyrin IX under oxidizing conditions (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A crucial branch point of the tetrapyrrole synthetic pathway in higher plants is the chelation of either Mg 2ϩ to make chlorophyll or Fe 2ϩ for heme catalyzed by magnesium chelatase or ferrochelatase, respectively (38). One model that has been proposed for the control of this branchpoint, based on biochemical studies, is that the two enzymes are spatially separated within the chloroplast, magnesium chelatase being associated with the envelope membrane (39), and ferrochelatase existing exclusively in the thylakoids (40).…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood that its final destination is the thylakoids is increased by the recent reassignment of another Chl-biosynthetic enzyme, Pchlide reductase, to the thylakoids [54,55]. Interestingly, Pchlide reductase had previously been reported to be on the chloroplast envelopes [48], but this has now been explained as an import intermediate [56], and the final destination of this enzyme is thought to be the thylakoids [54,55]. Only two other porphyrin-biosynthetic enzymes have been reported to be on the envelope : protoporphyrinogen oxidase (which functions in both haem and Chl synthesis) [49] and ferrochelatase [57].…”
Section: Localization Of Mg-chelatase Within the Chloroplastmentioning
confidence: 99%